A Comparative Study: The Banking Reforms in Indonesia, Thailand, the US, and the UK, and How it Affected the Banking Performance and the Economic - dhanny dhanny; Berri Brilliant Albar (Management Institute Faculty of Economics Universitas Andalas, 2023)
The banking crisis occurred as a result of the massive financial deregulation that lead the banks to expand their businesses on the large-scale and tends to increase the risk their portfolio, such as in the Asian and the US crisis. The aftermath of the crisis became the challenge for the government and regulators, as it required a tremendous amount of liquidity injection either from the international lender of last resort such as the IMF, or from the government (by using taxpayers money), undeniably it remains painful for the economic recovery. The banking reforms aim to strengthen the banks and the financial industry. There are numerous reforms agenda in every crisis, however this study focus on several issues that most often arises in every crisis. The most common issues are; (1) the presence of deposit insurance institution protecting the depositor's money to reducing public panics, and bank runs, (2) ensuring sufficient capital as a buffer to the crisis and liquidity management by adopting the Basel requirements. By comparing the banking reforms in the US, the UK, Indonesia, and Thailand, this study aims to give insight which reforms were the most effective to address the crisis and had an impact to the bank's performance, particularly in the profitability and also the economic performance, by measuring loan to GDP ratio. The result of this research are the banking reforms to some extent, have had a positive impact on the banking profitability in emerging countries. However, in the developed countries, the financial crisis and the banking reforms were not necessarily affected the recovery of the industry. Meanwhile, the banking reforms that focus on strengthening the regulation could slow down the economic growth as the banks become more prudent in giving the new loan. However, lowering the net interest margin could boost the lending growth. In the end, the policies recommendation are implementing the risk-based premium scheme on deposit insurance institution, and the implementation of counter-cyclical capital variation on the capital requirement.